2015
DOI: 10.1039/c5ra08714g
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparison of uniform hydrophilic/hydrophobic transparent silica aerogel beads: skeleton strength and surface modification

Abstract: Hydrophilic mesoporous sodium silicate-based silica aerogel beads were produced by skeleton improvement of wet silica beads by ambient pressure drying. This preparation method is suitable for economic and large-scale industrial production of silica aerogel beads. AbstractSilica aerogel is a kind of good adsorbents due to the large surface areas and chemical stability. However, its inherent poor mechanical properties and hydrophobicity limited applications in water treatment. To improve the adsorption performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 32 publications
(55 reference statements)
0
18
0
Order By: Relevance
“…The need to recycle hydrophilic silicas may be considered irrelevant if the absence of functionalising agents and the use of cheaper precursors and synthesis make the production and waste management of these materials economically suitable for a single adsorption cycle, hence, removing regeneration costs and associated issues. Such gains may be achieved by using simpler, less energy intensive processing methods and low cost synthetic routes using ambient pressure drying are already known to produce silica aerogels, from waterglass, with excellent mechanical properties (Zong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The need to recycle hydrophilic silicas may be considered irrelevant if the absence of functionalising agents and the use of cheaper precursors and synthesis make the production and waste management of these materials economically suitable for a single adsorption cycle, hence, removing regeneration costs and associated issues. Such gains may be achieved by using simpler, less energy intensive processing methods and low cost synthetic routes using ambient pressure drying are already known to produce silica aerogels, from waterglass, with excellent mechanical properties (Zong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The longer hydrolysis-ageing time gave rise to the tendency to reduce silanol groups. FTIR spectra of the surface modification of MS with TMMS as demonstrated in Figure 5 b revealed the presence of Si–CH 3 at 2860 cm −1 [ 24 ]. The reduction of hydroxyl group intensities around 3300–3500 cm −1 also implied that some modification took place.…”
Section: Resultsmentioning
confidence: 99%
“…53 The high transparency of all the TEAH catalyzed aerogels indicated that the pores and particles present in the aerogels are regular and small enough. 54 In addition, the transmittance of all the TEAH catalyzed aerogels in UV region is close to zero indicating a strong scattering of short light waves.…”
mentioning
confidence: 93%